Challenges for Marketing Research in the Concept of Sustainable Development - Sousa, Bruno (2021)
Sustainability is a topic that is currently being discussed and constantly adapting, since it is related not only to an ecologically correct posture and strategy but also economically viable and socially equitable. Therefore, the importance given by the media to the theme of ecology, sustainability has led to a growing concern among the population. This concern leads to greater environmental awareness (Ngo et al., 2018), which ends up influencing the purchase, that is, they verify whether a product is ecological and compatible with sustainability (Pinto da Silva et al., 2019). For instance, regarding the environment, it promotes incentives for the preservation of nature, education on environmental ethics, and the defense for the preservation with development within the environmental perspective.